Asuhan Keperawatan Pada Ny. S Dengan Post Operasi Sectio Carsarea Indikasi Partus Tak Maju Di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Futuhatil Ilahiyah; Tati Karyawati; Siti Fatimah (An-Najat, 2023)
Labor and birth are physiological events, during the birth process the baby, placenta and membranes are expelled from the uterus through the birth canal. Women who are facing labor definitely want their labor to go smoothly and give birth to a perfect baby. However, it is not uncommon for the birthing process to experience obstacles and a surgical procedure, namely Sectio Caesarea, must be carried out, either due to considerations of saving the mother and fetus or the patient's personal wishes (Ramadhanti et al, 2022).